2000
DOI: 10.1074/jbc.275.4.2877
|View full text |Cite
|
Sign up to set email alerts
|

Homodimer of Two F-box Proteins βTrCP1 or βTrCP2 Binds to IκBα for Signal-dependent Ubiquitination

Abstract: We found previously that overexpression of an F-box protein ␤TrCP1 and the structurally related ␤TrCP2 augments ubiquitination of phosphorylated IB␣ (pIB␣) induced by tumor necrosis factor-␣ (TNF-␣), but the relationship of the two homologous ␤TrCP proteins remains unknown. Herein we reveal that deletion mutants of ␤TrCP1 and ␤TrCP2 lacking the F-box domain suppressed ubiquitination and destruction of pIB␣ as well as transcriptional activation of NF-B. The ectopically expressed ␤TrCP1 and ␤TrCP2 formed both ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 49 publications
3
103
0
Order By: Relevance
“…The prevailing view is that the dimerization is mediated by F-box proteins, including Fbw7 and Fbw1/ ␤TrCP, and provides a preferable conformation for attachment of ubiquitin to the substrates or facilitates interaction with the substrates (57,58). Recently, Chew et al (59) reported that CUL1 dimerized in a substrate recognition subunit-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing view is that the dimerization is mediated by F-box proteins, including Fbw7 and Fbw1/ ␤TrCP, and provides a preferable conformation for attachment of ubiquitin to the substrates or facilitates interaction with the substrates (57,58). Recently, Chew et al (59) reported that CUL1 dimerized in a substrate recognition subunit-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…For hTrCP1 and hTrCP2, it has been reported that the heterodimers are unable to bind substrate protein; in this way, dimerization might regulate substrate ubiquitination (28). The role of the heterotypic interaction with Fbw7 variants is complicated by the differential localization of each (12).…”
Section: Discussionmentioning
confidence: 99%
“…Other F-box proteins have been shown to form dimers; indeed, the D domain derives its name from its role in hTrCP dimerization (28). Fbw7 and its homologues in model organisms exhibit significant homology to the D domain and it is interesting that this domain appears in only a subset of F-box proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations